2003
DOI: 10.1046/j.1542-474x.2003.08306.x
|View full text |Cite
|
Sign up to set email alerts
|

ST Segment Analysis by Holter Monitoring:

Abstract: The outcome of Holter analysis for ischemic events is greatly dependent upon how an ischemic event is defined. Consensus on how to define an ischemic event is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Various study groups have taken a different view as to whether the ST segment analysis of patients with initially reduced ST segment provides additional information. Some exclude these patients from the evaluation, whereas others include them and specify an ST depression of -0.1 or -0.2 mV in addition to the baseline ST depression [28]. The ST level that is recorded in a short time interval after the investigator had put the ECG electrodes in place, however, is designated as the baseline ST level.…”
Section: Discussionmentioning
confidence: 99%
“…Various study groups have taken a different view as to whether the ST segment analysis of patients with initially reduced ST segment provides additional information. Some exclude these patients from the evaluation, whereas others include them and specify an ST depression of -0.1 or -0.2 mV in addition to the baseline ST depression [28]. The ST level that is recorded in a short time interval after the investigator had put the ECG electrodes in place, however, is designated as the baseline ST level.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Bjerregaard and colleagues showed that detecting ischemic events 80 ms after the J-point instead of 60 ms, used in this study, increased the number of ischemic events because most of these events are down-sloping 20. The inclusion criteria of 0.1 mV J-point depression will also reduce detected ischemic events.…”
Section: Discussionmentioning
confidence: 77%
“…The visual interpretation included the whole tape and parts of interest were printed out at 25 mm/sec speed for analyses of STDE and arrhythmia in relation to heart rate in order to identify possible positional ST changes, especially during night. ST segment changes was defined as >0.1 mV (1 mm) planar or down-sloping shift from the isoelectric baseline occurring at 60 milliseconds after the J point, with the midpoint of PR as a reference and with a duration of at least ≥1 minute 20. The maximal STDE was defined as the maximum value registered by the recorder.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for an ST-depression and ST-elevation were 0.1 mV flat or down-sloping morphology with deviated J-point. 10 Standard postoperative 12-lead ECGs were made on days 3, 7, and 30, and/or at discharge, and whenever clinically indicated.…”
Section: Methodsmentioning
confidence: 99%